AXL Overexpression in Tumor-Derived Endothelial Cells Promotes Vessel Metastasis in Patients With Hepatocellular Carcinoma - Chai, Zong-Tao; Zhang, Xiu-Ping; Ao, Jian-Yang; Zhu, Xiao-Dong; Wu, Meng-Chao; Lau, Wan Yee; Sun, Hui-Chuan; Cheng, Shu-Qun (Frontiers in Oncology, 2021)
Portal vein tumor thrombus (PVTT) is one of the most serious forms of hepatocellular carcinoma (HCC) vessel metastasis with poor survival. However, the molecular mechanism of PVTT has not been elucidated yet. In this study, the effect and molecular mechanism of AXL expressed in the tumor-derived endothelial cells (TEC) on vessel metastasis was investigated. In present study, high AXL expression was seen in TECs, but not in tumor cells of HCC patients with PVTT and this was associated with poor overall survival (OS) and disease-free survival (DFS) of these patients. AXL overexpression was positively associated with CD 31 expression both in vitro and in vivo. AXL promoted the cell proliferation, tube formation, and migration of both TECs and normal endothelial cells (NECs). High expression of AXL in TECs promoted cell migration, but not proliferation of HCC cells. Further studies demonstrated that AXL promoted cell migration and tube formation through the activation of PI3K/AKT/SOX2/DKK-1 axis. AXL overexpression in HUVECs promoted tumor growth and liver or vessel metastasis of HCC in xenografted nude mice, which could be counteracted by R428 (an AXL inhibitor). R428 reduced tumor growth and CD 31 expression in HCC in PDX xenograft nude mice. Therefore, AXL over-expression in TECs promotes vessel metastasis of HCC, indicating that AXL in TECs could be a potential target for therapy of HCC patients with PVTT.